The Use of Factorial Design for Analysis of Mercury Removal Efficiency Using Palm Oil Fuel Ash - Imla Syafiqah, Mohd Salleh; Hafizuddin, Wan Yussof (Volkson Press Sdn Bhd, 2018)
A two-level half fractional factorial design was employed to evaluate the factors that have the greatest effect on the mercury removal efficiency. Several factors can influence the mercury removal using palm oil fuel ash (POFA). The aim of this study was to examine the main and interaction effects on mercury removal efficiency using POFA. The parameters which affect the mercury removal are pH (2 – 6), contact time (1 hr – 4 hr), initial concentration of the Hg2+ solution (1 mg/L – 5 mg/L), adsorbent dosages (0.10 g – 0.25 g) and agitation speed (100 rpm – 200 rpm) were investigated. Half factorial design using Response Surface Methodology (RSM) was used to determine the significant contribution of the above factors towards mercury removal efficiency. From the statistical analysis, the main factor of contact time and the interaction between adsorbent dosage and initial concentration of the Hg2+ resulted in the strongest effect on mercury removal. However, the interaction between agitation speed and pH was the least influencing factors. Based on the predicted and the experimental results presented, the experimental values were in good agreement with the predicted values proposed by the model with an error less than 10 % and proved to be an adequate model. The result indicated that fractional factorial design (FFD) was useful to improve the mercury removal efficiency by considering all the interactions of variables involved. In summary, this demonstrated that POFA could be potential as low-cost adsorbent for the removal of mercury.